Relationships between Parents’ Marital Quality, Family Environment and Students’ Behaviour of Selected Secondary Schools in Selangor and Kuala Lumpur, Malaysia - Lai, Chooi Seong (Annie) (2008)
The objective of this research was to assess the differences and relationships between parents’ marital quality and family environment of two hundred Form 4 delinquent and non-delinquent secondary school students in Selangor and Kuala Lumpur, Malaysia. A final research model for parents’ marital quality and family environment of students was finally established. Parents’ marital quality was measured by Dyadic Adjustment Scale (Spanier & Lewis, 1976), Family environment of students was assessed by Family Environment Scale (Moos & Moos, 1981, 2002), and behaviour of students (delinquent and non-delinquent acts) was assessed by a set of self-report instrument established by Rozumah, Rumaya, Asnarulkhadi, Amna, Mansur, and Tan (2003). Independent-samples t-tests reported significant differences in the family cohesion, family expressiveness, family conflict, and family achievement orientation of delinquent and non-delinquent students. Pearson product-moment correlation coefficient concluded that there were significant positive correlations between parents’ dyadic satisfaction, parents’ marital quality, family cohesion, expressiveness, conflict, relationship dimensions, achievement orientation and active-recreational orientation with students’ behaviour. The final regression model indicated by binary logistic regression analysis showed that the predictor variables which had contributed significantly to the model were firstly, family conflict, followed by family cohesion, family members’ achievement orientation, then parents’ dyadic satisfaction, and lastly family members’ expressiveness. Future studies should focus on parents’ and family communication, conflict resolution, personality, financial management, leisure activities, parenting styles, extended family, and family adaptability. This study reiterated the importance of maintaining positive marital quality in married couples and positive family environment for children’s well-being. Parents must realize that adolescents need their parents’ companionship, care and to be active listeners to their emotions, achievements and problems.